A time-motion analysis of elite solo synchronized swimming - Alentejano, T.; Marshall, D.; Bell, G. J. (International Journal of Sports Physiology and Performance, 2008)
Purpose: To determine the total amount and relative time periods of face immersion (FI) in a synchronized swimming solo routine and the relationship between FI, distance covered, and the technical-merit score of the 11 top Canadian soloists at a synchronized swimming national championship (mean age 20 ± 1.8 y, height 173.3 ± 4.1 cm, and body mass 58.3 ± 4 kg). Methods: Videotape and timing of solo performances combined with manual tracking of pool patterns. Results: Analysis of performance revealed that an average of 18 FI periods, mean of 6.8 s, were performed for an average total time of 133.7 ± 27.1 s (range 102.2 to 199.8 s). The average longest FI time period was 25.45 ± 6.2 s (range 18.18 to 38.72 s), and most (10/11) of these were in the first third of the solo. The mean total horizontal distance covered was 57.61 ± 6.84 m (range 48.61 to 68.2 m), and the total horizontal distance covered relative to time was 0.276 ± 0.034 m/s (range 0.235 to 0.340 m/s). No significant relationships were found between any of the FI periods and the distance covered or between the technical-merit score and FI periods. Each solo contained 6 to 8 underwater sequences, none of which were longer than 40 seconds, the cutoff deemed dangerous by FINA (Fédération Internationale de Natation). Conclusion: This study shows that the times underwater for solos in Canada are within safety limits recommended by FINA and that judging in Canada is not related to underwater periods of swimming.